2021
DOI: 10.3390/geosciences11030126
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Effect of Soil Properties on Bio-Accessibility of As and Pb from Human Ingestion of Contaminated Soil

Abstract: Exposure to soils contaminated with heavy metals can pose human health risk to children through ingestion of contaminated soil. Soil properties such as soil pH, reactive Fe and Al oxide content, clay content, soil organic matter (SOM), and cation exchange capacity (CEC) can reduce contaminant bio-accessibility and exposure. In vitro bio-accessibility (%IVBA) of As and Pb in 19 soils was determined using U.S. EPA Method 1340. Soil properties reduced the bio-accessibility of As by 17–96.5% and 1.3–38.9% for Pb. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The influence of different P amendments, limited reported soil properties, and variety of methods employed diminished the ability of this study to determine the effect of soil properties. Studies have found significant correlations between bioaccessible Pb and soil properties ( 60 ) but this has not been researched specifically for soils remediated with P amendments. Further primary research is needed to ascertain the influence of soil properties on the ability of P to reduce bioaccessible soil Pb.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of different P amendments, limited reported soil properties, and variety of methods employed diminished the ability of this study to determine the effect of soil properties. Studies have found significant correlations between bioaccessible Pb and soil properties ( 60 ) but this has not been researched specifically for soils remediated with P amendments. Further primary research is needed to ascertain the influence of soil properties on the ability of P to reduce bioaccessible soil Pb.…”
Section: Discussionmentioning
confidence: 99%
“…After amending a soil to reduce Pb or As lability, the efficiency needs to be demonstrated, and chemical characterization protocols are commonly used. Various chemical methods have been tested to evaluate Pb and As mobility and bioavailability to mammals, plants, and microorganisms (Beyer et al., 2016; Lake et al., 2021). Total elemental concentration (e.g., USEPA Method 3050b; USEPA, 1996) is routinely used for risk assessment but is a poor indicator of bioavailability.…”
Section: Introductionmentioning
confidence: 99%